Laparo-endoscopic Hernia Surgery Evidence Based Clinical Practice (Springer Berlin Heidelberg, 2018)
This book is distinctive in that it focuses exclusively on current laparoscopic and endoscopic techniques for inguinal, primary and incisional abdominal wall, and hiatal hernias. Individual steps in diagnosis and treatment are described by experts in the field, but this clinical expertise is also integrated with the best available external evidence from systematic research as encapsulated in statements, recommendations, and guidelines. The reader will thus not only learn how to perform techniques systematically and reproducibly but also come to understand which of the procedures have been scientifically validated by studies, reviews, and meta-analyses and which have simply developed empirically. The descriptions of technique are supplemented by detailed guidance on such aspects as indications, anesthesia, aftercare and pain management, and the prevention and management of complications. Where appropriate, careful comparisons are made of competing repair options, including open techniques. In summary, this book will help practicing surgeons to standardize their operative technique so as to reflect current scientific knowledge and thereby improve the quality of laparoscopic/endoscopic hernia surgery.